Implementation of the Policy on the Assessment System for Prisoner Development in the Ternate State Detention Home - Cindy Arnidayanti Dwi Setiawan (Journal Research of Social Science, Economics, and Management, 2025)
The low participation in sports of the Indonesian people (Sports Community Participation Index/IPMO 0.263 in 2024) is caused by multidimensional factors such as the economy, time, and health literacy, requiring evidence-based and collaborative policies. This research aims to formulate a cross-sectoral strategy to build a sports ecosystem that supports the Indonesia Fitar 2045 target. This study uses an Evidence-Based Policy  approach with primary (interview) and secondary (BPS, policy) data analysis, as well as evaluation through Cost-Benefit Analysis (CBA) and Regulatory Impact Assessment (RIA). Integrated policies (regulations, infrastructure, community empowerment, and educational integration) have proven to be effective if supported by economic incentives, digital technology, and local wisdom approaches. These policy recommendations require phased implementation (2025–2029) with close monitoring to address access inequality and increase participation. Further research needs to evaluate the socio-economic impact and role of the private sector.